CHEMICAL DEPRECIATION OF CUSO4, NAPCP AND BAYLUSCIDE IN STANDING WATER - J.Massoud; F.Arfaa; Chu; K. Y (Tehran University of Medical Sciences, 1973)
In an attempt to determine the chemical losses of three common molluscicides, i.e. CuSO4, NaPCP and Bayer -73, in stagnant water, a solution of each of this molluscicide was applied to one or more B.truncatus habitats and outdoor aquariums. The concentration of each molluscicide in these water bodies was determined immediately after application and at fixed time intervals thereafter. The concentration of copper sulfate dropped dramatically to 50% within 1 ½ hours after application. This fast depreciation is attributed to the alkalinity of the natural waters in this area. The depreciation of NaPCP, although slower than copper sulfate, was faster than Bayluseide. As this fast depreciation is caused by sunlight, NaPCP is not recommended for use in Khuzestan (Iran).Since the effect of Bayluscide on snails was also superior to that of the other two mollluscicides, Bayer-73 can be considered as the molluscicide of choice for snail control in Iran.